PROGRAM STUDI S1 AKUNTANSI FAKULTAS EKONOMI UNIVERSITAS STIKUBANK SEMARANG 2012 - Eni Setiyowati, 08.05.52.0094; Suwarti, Titiek (Students Journal of Accounting and Banking, 2012)
This study is a study that tested the profitability, company size and outsider ownership terhadapa period presentation and announcement period. Signal in accordance with the theory that an action taken by management to provide guidance to investors about how the management of the companys prospects look, with a signal - a signal success or failure of management (agent) who presented to the owner (principal).Based on the theory that the signal to see a signal - a signal success or failure of the company, the company tried to publish financial statements have been audited to the public in anÂ  accurate and timely. In this study, this study used a purposive sampling and obtain samples of 279 samples of the company. By using multiple regression analysis to explain the relationship between these variables.The results of the test is the test statistic indicates only the size of the company are significantly negative effect on the presentation period, while profitability and outsider ownership does not affect the span of just presenting Retrieved ukuan companies are significantly negative effect on the announcement period, while profitabilias and outsider ownership does not affect the announcement periodKeywords: range of time of presentation, the announcement period, profitability, firm size, outsider ownership.